Q&A: ICTs and the post-harvest fishing industry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
How are ICTs being used to support post-harvest fishing activities? Venu Pidachy explains how, in order to comply with strict international food safety and quality regulations, the Ugandan Nile perch exporter Marine Products Ltd is using methods originall